Prevalence, Risk Factors and Management of Morbus Hansen in Primary Health Care in Low Income Countries: A Comprehensive Systematic Review - Yulianto, Ronald; Gunawan, Ellen Aristika (International Medical Journal Corp. Ltd, 2024)
Background: Leprosy, also known as Hansen's disease, is a chronic infectious-contagious disease known to humankind since ancient times. It is characterized by predominant involvement of skin and peripheral nerves, caused by the Mycobacterium leprae (M. Leprae). Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The endemic regions of leprosy required strong commitments at both the national and international levels for leading to proper and accessible healthcare systems, improved sanitation and hygiene, well-maintained contact surveillance, and proper and timely delivery of treatment for those in need.